FRAMING THEORY : MEDIA DISCOURSE ANALYSIS OF PAKISTANI DRAMA “MAYI RI” - Hina Arif; Yumna Hassan Latki; Umna Tasleem; Hafsa Komal; Hiba; Aleeba Munawar (Dialogue Social Science Review (DSSR), 2025)
This study explores the portrayal of child marriage in the Pakistani drama Mayi Ri through the lens of Framing Theory. By employing a quantitative research design, data was collected via a structured Likert scale questionnaire distributed among viewers familiar with the drama. The findings reveal that Mayi Ri effectively uses framing techniques to raise awareness, challenge societal norms, and inspire critical reflection on the issue of child marriage. Key frames identified include victimization, societal pressure, empowerment, and social change, each contributing to a nuanced representation of the struggles faced by child brides. The drama’s resolution, emphasizing education, co-parenting, and mutual respect, was praised as progressive and impactful, encouraging viewers to reconsider harmful traditions. This study underscores the transformative potential of media in shaping public discourse and fostering social reform, illustrating how Mayi Ri serves as a powerful tool for addressing sensitive societal issues in Pakistan.